A desconstrução do conceito de saga na Teologia da Criação em Karl Barth - Souza Filho, Adilson de (2012)
What characterizes academic research in a doctoral course is that it should fulfill two fundamental requirements. The first is the element of innovation, the ability to enrich research on the theme. The second is that it should promote new ways of reading. We therefore believe that this thesis has met the expectation, the innovative element of this research being the deconstruction of the concept of the creation saga proposed by Karl Barth. It is new because we could not find, as we had suspected, any author, or even work or research that proposed to face the same task. Instead, there are even some authors that highly praise the research conducted by Karl Barth, as is the case of Coats and Brueggemann. Although they respond to some points of Barth s theology, they did not specifically deal with the concept of saga. The second aspect, structurally related to the first, is that it promotes new possibilities of reading. Using the approach of Paul Ricoeur, we propose a new biblical hermeneutics, based on what this author calls a long way, which makes use of various methods, including the historical-critical, to seek an interpretation of the text world which manages to make sense of the world outside the text. We believe that this proposal can overcome the purely dogmatic reading of the text world. According to Ricoeur, we believe that the foundational elements that guided the hermeneutic of Dasein, or even around the subject/object relation can contribute to a new hermeneutic, since it does not make the same concessions to the knowing subject. Thus, the possibility of a new reading appears from what Ricoeur has defined in dialectical relationship between the text world and the world outside the text, as a transforming and revelant representation. And this is where the Holy Scriptures has the the position of source of revelation and inspiration.